FENSPIRID FOR CURING ACUTE RESPIRATORY INFECTION OF INFANTS - G.A. Samsygina ("Paediatrician" Publishers LLC, 2007)
The article is about fenspirid (Erespal) medication to combat acute respiratory infections (ARI) of infants. 94 children aged 1-3 suffering from ARI were observed: of them 64 took fenspirid, 30 children didn't take it (the control group). The research has revealed that fenspirid reduces ARI manifestation even if ARI proceeds along with ordinary or obstructive bronchitis - accordingly, fenspirid can be recommended for a wider usage to cure ARI of infants up to 3 years of age.Key words: fenspirid, infants up to 3 years of age, acute respiratory infection.